(untitled) (Texas Journal of Medical Science, 2023)
Assessing the quality of surface waters and estuaries and monitoring soil health are critical to monitoring and maintaining the health of aquatic ecosystems and ensuring sustainable land management practices. This involves the assessment of various parameters, such as chemical composition, physical characteristics and biological indicators, to determine the overall condition and potential impact on human health and the environment